2006
DOI: 10.1158/0008-5472.can-05-3940
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Transcriptional Inhibitor Induces Apoptosis in Tumor Cells and Exhibits Antiangiogenic Activity

Abstract: Using a high-throughput cell-based assay, we identified a nucleoside analogue 4-amino-6-hydrazino-7-B-D-ribofuranosyl-7H-pyrrolo(2,3-d)-pyrimidine-5-carboxamide (ARC), which has the properties of a general transcriptional inhibitor. Specifically, ARC inhibits the phosphorylation of RNA polymerase II by positive transcription elongation factor-b, leading to a block in transcriptional elongation. ARC was able to potently repress p53 targets p21 and hdm2 (human homologue of mdm2) protein levels, but dramatically … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
67
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 44 publications
5
67
0
Order By: Relevance
“…Previously, we had characterized ARC on a number of cancer cell lines of epithelial origin (Radhakrishnan and Gartel, 2006b). In this study, we have extended these studies on neuroblastoma cell lines and found that these cells are susceptible to ARC in nanomolar concentrations.…”
Section: Targeting Akt In Neuroblastoma Cells Sk Radhakrishnan Et Almentioning
confidence: 60%
See 3 more Smart Citations
“…Previously, we had characterized ARC on a number of cancer cell lines of epithelial origin (Radhakrishnan and Gartel, 2006b). In this study, we have extended these studies on neuroblastoma cell lines and found that these cells are susceptible to ARC in nanomolar concentrations.…”
Section: Targeting Akt In Neuroblastoma Cells Sk Radhakrishnan Et Almentioning
confidence: 60%
“…Furthermore, we observed that ARC was able to induce the cleavage of caspase-3 in NB-1691 and IMR32 cell lines at B10-fold lower concentration than DRB (Figure 1d). The significant difference in apoptosis, despite their similarity in the degree of transcriptional inhibition (Radhakrishnan and Gartel, 2006b) suggests that ARC may employ more than transcriptional repression to induce apoptosis in these neuroblastoma cell lines.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, we had reported that ARC (4-amino-6-hydrazino-7-b-d-ribofuranosyl-7H-pyrrolo[2,3-d]-pyrimidine-5-carboxamide), a small molecule inhibitor of P-TEFb kinase (Cdk9/CyclinT1 complex) and a transcriptional inhibitor with anticancer properties, increased p53 levels although simultaneously repressing its target genes (Radhakrishnan and Gartel, 2006b) similarly to the well-known anticancer drug flavopiridol (Demidenko and Blagosklonny, 2004). We also found that p53 may be phosphorylated by P-TEFb and ARC inhibits phosphorylation of p53 by P-TEFb kinase in vitro (Radhakrishnan and Gartel, 2006a).…”
mentioning
confidence: 99%